PNAB 2017 and the number of community health agents in primary care in Brazil - Deborah Ellen Wanderley Gomes Freire; Aldelany Ramalho Freire; Edson Hilan Gomes de Lucena; Yuri Wanderley Cavalcanti (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To analyze the effect of the 2017 Basic Primary Care Policy (PNAB) on the number of community health agents per primary health care team. METHODS: This is a cross-sectional, descriptive and analytical study using data available on the Ministry of Health platform called e-Gestor da Atenção Básica, about Brazil's 5,570 towns between October 2017 and December 2019. The survival of the number of towns that did not reduce the number of community health agents was analyzed according to region of the country, the Human Development Index (HDI), the Gini Inequality Index and population size. Cox regression was used to analyze the factors associated with a reduction in the number of CHAs after one month and, from then on, every three months until two years had passed since the publication of the 2017 PNAB Ordinance, considering p < 0.05. CONCLUSIONS: After two years, the greatest reduction was observed in towns in the Midwest and South regions, which presented a high HDI, lower inequality and larger populations. Towns in the Midwest (HR = 1.256) had a higher chance of reducing the number of CHAs compared to the North region. Towns with a higher HDI (HR = 1.053) and larger population size (HR = 1.186) were also more likely to reduc the number of community health agents. Therefore, after the 2017 PNA, the number of towns reducing the amount of community health workers in primary health care increased over the months